An automated gravimetric & PWM based fluid dispensing system with GA parameter fine tuning - Sim E.Y.S.; Koh S.P.; Tiong S.K.; Yap B.K. (2023)
In this paper we present a gravimetric and Pulse Width Modulation (PWM) based fluid dispensing technique for a maximum dispense batch of 30kg. In addition, a Genetic Algorithm (GA) Parameter Fine Tuning technique is presented as well. Based on the combination of both techniques, the system is able to dispense up to 50 samples with an accuracy of +/- 2g with the dispensing speed varies between 50 seconds to 60 seconds for a 5.2kg batch within one dispense valve. The reported dispensing technique is based on PWM technique in the dispensing sequence and GA technique in the parameter fine tuning. This technique could overcome limitations of the volumetric dispensing and manual parameter tuning presently applied in the coatings industry. The fast and accurate system which is modularly built out of individual dispense valve is able to handle different fluids with varying viscosity. The working principles of the system as well as its accuracy results are presented. 2009 IEEE.